Detection of IgA and IgM antibodies to HIV-1 in neonates by radioimmune western blotting. Issue 6841 (13th June 1992) - Portincasa, P.; Conti, G.; Re, M. C.; Chezzi, C.
Abstract : OBJECTIVE--To detect infection with HIV-1 by IgA and IgM response at birth in children born to HIV-1 seropositive mothers. DESIGN--Western blotting and radioimmune western blotting on stored sera from infected and uninfected babies born to HIV-1 seropositive mothers. Sera were pretreated to remove IgG. SETTING--Parma and Bologna, Italy. SUBJECTS--12 infected and five uninfected babies born to HIV-1 seropositive mothers and three babies born to seronegative mothers. MAIN OUTCOME MEASURES--Effectiveness of western blotting and radioimmune western blotting in detecting antibodies to HIV-1 gene products. RESULTS--With conventional western blotting we found IgA class antibodies to HIV-1 proteins in serum from three out of 12 infected children; in two of these three the serum was collected at age 3 months (positive controls). Radioimmune western blotting detected both IgA and IgM antibodies in serum from all infected children tested, whereas all serum from uninfected children born to seropositive and seronegative mothers showed no such antibodies. CONCLUSION--Although the technique should be tested on more patients, radioimmune western blotting seems to be a valuable tool for serological diagnosis of congenital HIV-1 infection at birth in neonates born to seropositive mothers.